Implications of DNA damage repair alterations for the management of prostate cancer. Issue 3 (9th May 2022) - Lozano, Rebeca; Olmos, David; Castro, Elena
Abstract : Purpose of review: In this review, we summarize the prevalence of alterations in DNA damage repair (DDR) genes in prostate cancer, their clinical significance, the therapeutic strategies developed to take advantage of the impaired tumour ability to repair DNA and the diagnostic approaches available to identify patients likely to benefit from DDR-targeting agents. Recent findings: DDR alterations are more frequent in metastatic than in localized prostate cancer and some of them associate with aggressive disease whereas the significance of others remain unclear. The most appropriate management approach for DDR-defective prostate cancer patients is unknown. Clinical trials have demonstrated the efficacy of different poly-ADP ribose polymerase inhibitors (PARPi) to treat metastatic castration-resistant prostate cancer patients with BRCA1/2 alterations, although there may be other DDR alterations that sensitize patients to these drugs. Multiple strategies to target DDR defects are being investigated, including PARPi in combination, platinum-based chemotherapy and immunotherapy, both in earlier and late disease stages. Optimization of molecular testing is paramount for the implementation of precision oncology in prostate cancer. Summary: Certain DDR defects present in prostate cancer have prognostic and therapeutic implications whereas the significance of other DDR alterations is yet to be elucidated.